2018
DOI: 10.2134/agronj2017.12.0680
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the CROPGRO Model to Simulate Alfalfa Growth and Yield

Abstract: Despite alfalfa's global importance, there is a dearth of crop simulation models available for predicting alfalfa growth and yield with its associated composition. The objectives of this research were to adapt the CSM-CROPGRO Perennial Forage Model for simulating alfalfa growth and yield and to describe model adaptation for this species. Data from six experimental plots grown under sprinkler irrigation in the Ebro valley (Northeast Spain) were used for model adaptation. Starting with parameters for Bracharia b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…Alfalfa cultivars grown in optimal conditions have shown SLA values ranging between 250 and 460 cm 2 g −1 [41], which is in agreement with the range of variation observed in this work, excluding the values of the diploid materials (caerulea; Table 2). SLA is a morphological trait strongly associated with alfalfa drought tolerance [36,42].…”
Section: Phenotypic Diversitysupporting
confidence: 91%
“…Alfalfa cultivars grown in optimal conditions have shown SLA values ranging between 250 and 460 cm 2 g −1 [41], which is in agreement with the range of variation observed in this work, excluding the values of the diploid materials (caerulea; Table 2). SLA is a morphological trait strongly associated with alfalfa drought tolerance [36,42].…”
Section: Phenotypic Diversitysupporting
confidence: 91%
“…This helped pave the way for research into ML and crop prediction [20]. In 2018, Malik et al [21] highlighted the global importance of alfalfa and demonstrated that ML techniques can be useful when predicting yields, as they adapted the CROPGRO model to predict alfalfa yields. Jing et al [22] continued this research with their 2020 adaptation of CROPGRO tailored to predicting alfalfa in Canada.…”
Section: Related Workmentioning
confidence: 99%
“…Meanwhile, independent plots of wheat (n = 4), barley (n = 7), maize-LS (4), maize-SS (n = 4) and sunflower (n = 4) data were used for model evaluation corresponding to the 2015-2016 crop season. In the case of alfalfa, Malik et al (2018) has already adapted the DSSAT model for simulating alfalfa growth and yield using a dataset collected under the same conditions as those in the current study area.…”
Section: Dssat Model Description Calibration and Evaluationmentioning
confidence: 99%
“…For the irrigation management evaluation of each representative crop in the VID, the corresponding calibrated model was applied to compare the current farmers' irrigation management methods (the real irrigation dates and depths applied by the farmers were obtained from the Almudévar Water User Association for each plot and crop season) and the optimal irrigation management scenarios. In the case of alfalfa, the field experiment performed in the VID during 2015 and 2016, as described by Malik et al (2018), was used for scenario application.…”
Section: Irrigation Scenariosmentioning
confidence: 99%
See 1 more Smart Citation